2014
DOI: 10.1007/s10620-014-3457-z
|View full text |Cite
|
Sign up to set email alerts
|

Significance of IL-1RA Polymorphism in Iranian Patients with Inflammatory Bowel Disease

Abstract: IL-1 SNPs seem to be associated with IBD and could affect the disease severity as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…3c ). Many of these cytokines (or their receptors or ligands) have been associated with genetic susceptibility to IBD or have been suggested as drug targets for IBD, including TNF-α ( ref 45 ), IL-6 ( ref 46 ), IL-1RA 47 , CXCL10 ( ref 48 ), and IL-12Rp40 ( ref. 12 ) ( Supplementary Table 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…3c ). Many of these cytokines (or their receptors or ligands) have been associated with genetic susceptibility to IBD or have been suggested as drug targets for IBD, including TNF-α ( ref 45 ), IL-6 ( ref 46 ), IL-1RA 47 , CXCL10 ( ref 48 ), and IL-12Rp40 ( ref. 12 ) ( Supplementary Table 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…Discordant results regarding the associations between IL1RN genetic variants and IBD have been published. Some studies reported significant associations with CD [ 34 , 35 ] and UC predispositions [ 36 , 37 ], treatment outcome [ 38 ], and age at the onset [ 39 ]; on the contrary, other studies did not find any associations [ 40 42 ]. Interestingly, IL-1RN ∗ 2 variant has been associated with reduced levels of IL-1ra protein and IL-1RN mRNA in the colonic mucosa from UC patients [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such difference scored OR value of 1.76. A previous investigation carried out a similar determination in Iranian IBD patients, and IL1RA mspa 1110 CC genotype was identified to have a positive association with CD, UC and IBD [18]. However, it is too early to reach a final conclusion about the role of IL1RA mspa 11100 SNP in pathogenesis of UC, and the observed association needs a confirmation.…”
Section: Discussionmentioning
confidence: 95%
“…Several SNPs have been described for IL1 genes and among these are IL1A −889 , IL1B −511 , IL1R1 pst1 1970 and IL1RA mspa1 11100 SNPs. Studies in CD and UC patients of different ethnicities have reported different correlations with the two forms of IBD, but some of them suggested that these polymorphisms may play a role in etiopathogenesis of IBD [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%